A NOVA EDUCAÇÃO PROFISSIONAL PARA O TRABALHO NO BRASIL NO SÉCULO XXI - Fonseca, Paulo Roberto Campelo Fonseca e (2015)
Demonstrate and purposes that vocational education takes on Brazil in the XXI Century is the objective of this work. To this was done a study of the Fordist State and his quest for full employment, as well as the post-Fordist and his search for employability State. In the Brazilian context showed how professional education becomes a means to the restructuring process in the passage from the twentieth to the twenty-first century. This transformation in education from Fordism to post-Fordism in your peripheral way in Brazil, mainly characterized by the increase in workers' education level guided in Toyotism, and changing a professional education focused on promoting only technical skill, one focused on the promotion of personal skills. Thus, presence up from the twenty-first century, the deployment of a new professional education that will meet the requirements of the new capital accumulation regime passing emerge in Brazil.